2000
DOI: 10.1046/j.1440-1746.2000.02198.x
|View full text |Cite
|
Sign up to set email alerts
|

Late biliary tract complications after orthotopic liver transplantation: Diagnostic and therapeutic role of endoscopic retrograde cholangiopancreatography

Abstract: These results confirms that ERCP is a valuable diagnostic tool and should be considered as the first step in the non-surgical management of late biliary tract complications after orthotopic liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 13 publications
0
31
0
1
Order By: Relevance
“…It constituted 28 (40%) of biliary complications in our patient group and half of these presented between 4-12 mo post OLT. Use of ERC for treating anastomotic stricture in older studies had been disappointing [36,37] , however newer studies have reported the efficacy of endoscopic and percutaneous approaches in managing these complications [5,36,[38][39][40] . 2 failures of endoscopic treatment for anastomotic stricture in the present study had to undergo hepaticojejunostomy after 7 and 8 mo of OLT.…”
Section: Discussionmentioning
confidence: 99%
“…It constituted 28 (40%) of biliary complications in our patient group and half of these presented between 4-12 mo post OLT. Use of ERC for treating anastomotic stricture in older studies had been disappointing [36,37] , however newer studies have reported the efficacy of endoscopic and percutaneous approaches in managing these complications [5,36,[38][39][40] . 2 failures of endoscopic treatment for anastomotic stricture in the present study had to undergo hepaticojejunostomy after 7 and 8 mo of OLT.…”
Section: Discussionmentioning
confidence: 99%
“…Biliary strictures may be anastomotic or non-anastomotic. Anastomotic biliary strictures are thought to result from technical surgical problems or local ischaemia; the incidence has been reported to be <10% for deceased donor liver transplantation, and to be higher, up to 30%, for living donor liver transplantation 153 154 155 156 157 158 159. Most anastomotic strictures appear within the first several months after transplantation, but they may also develop, less frequently, many years after transplantation.…”
Section: Later New-onset Diseases/injuries In the In Liver Allograftmentioning
confidence: 99%
“…Es werden zwei Entitäten von Strikturen unterschieden, die Anastomosenstenosen und die "ischemic type biliary lesions" (ITBL). Beide unterscheiden sich in ihrer Pathophysiologie und Prognose [5,7,8,9,12,13,14,15,16,17,18,20,21,22,23,24,25,26].…”
Section: Gallenwegsstrikturenunclassified